The Role of Architectural Landmarks in the City Identity of Pokhara - Thapa, Luna; Kandel, Samikshya (Technical Journal, 2024)
Pokhara, with its astonishing natural beauty, mysterious cultural heritage, religious sites, and adventure sports, embodies the essence of a tourist city. Recently declared as a tourism capital of Nepal, it stands as a testament to its allure and attractions. Architectural landmarks are also serving and emerging as popular tourist attractions. As architectural landmarks form a major part of tourism, their role in city identity should be recognized. This paper aims to study such architectural landmarks in terms of their role in city identity by analyzing three different cases from Pokhara, Nepal. Key informant interviews were held with officials from each landmark, along with a questionnaire survey of visitors. Data were analyzed quantitatively and qualitatively. The results show that architectural landmarks significantly contribute to the city's identity by providing a unique identity, complimenting natural beauty, discovering unexplored places, and providing settings for various activities. The study further unveils that the majority of visitors comprise domestic tourists, also emphasizes the significance of digital marketing and the visitors' opinion towards the addition of more architectural landmarks into the cityscape. Therefore, the study offers stakeholders with valuable insights into the potential of architectural landmarks to promote the identity of Pokhara as a tourist destination.